Physical Activity in Mental Health Disorders – Therapeutic Potential and Mechnisms - Wachowska, Maria; Rycąbel, Paweł Maciej; Romaniuk, Mateusz; Molenda, Marek Jarosław; Paniak, Mateusz; Sowiński, Wojciech Jan; Woszczyńska, Oliwia Brygida; Szymura, Marta; Wojciechowska, Agnieszka Ewelina; Krawczyk, Michał Brunon (Quality in Sport, 2025)
Introduction and Purpose: Mental health disorders are a global public health challenge, with rising emergency visits, especially among youth. Physical activity has gained recognition as an effective intervention for some mental disorders. PA positively affects mental health by enhancing neuroplasticity, neurotransmitter regulation, and reducing inflammation. Aerobic and resistance exercises, as well as yoga, are effective in alleviating depressive symptoms, anxiety, and PTSD, improving ADHD-related cognitive functions, and decreasing substance cravings. This study aims to analyze the influence of physical activity on mental disorders. Research Objective: The primary aim of this literature is to evaluate the impact of physical activity (PA) on mental health, focusing on depression, anxiety, PTSD, ADHD, and substance use disorders. Materials and Methods: A literature review of studies published from 2019–2024 in the PubMed database analyzed clinical trials, meta-analyses, and systematic reviews on the effects of PA, using the following keywords: “physical activity” ; “depression” ; “anxiety” ; “substance abuse” ; “adhd”. Conclusions: PA is an effective, accessible adjunct therapy for mental health conditions, providing significant physical and psychological benefits. Future research should prioritize optimizing intervention protocols, investigating long-term effects, and adapting treatments to the specific needs of diverse populations.